(untitled) (Journal of history, 2022)
In modern physical anthropology, a significant place is given to the study of the morphology of the dental system. Odontological data contain important information in the study of ethnogenetic processes of ancient and modern populations. In this article, for the first time, an odontological study of craniological materials from the Akterek burial ground, Zhambyl district of Almaty region, was carried out. Paleoanthropological materials from the excavations of the 2014, 2017 and 2021 field seasons were presented. As well as the archaeological data of the burials in which these materials were found. Based on a comparative typological analysis of the accompanying inventory, a historical chronology of these materials was carried out, which covers the period from the II century BC – I century AD to the VI-X centuries AD. The research program included 15 odontological, 2 odo-glyphic signs. Evaluation of signs and their analysis were carried out in accordance with the methodology and methodology of A.A. Zubov. The results of the study allow us to draw conclusions about the Caucasian, odontogenetic basis in the anthropological composition of the population of Akterek. The results of the study prove that the anthropological type of this period is very similar to the Saks of the early Iron Age of Central Kazakhstan, especially according to the signs of the western complex. The anthropological type of the Ak Terek series of the Turkic and ancient period belongs to the Western odontological complex, the Mongoloid elements are very poorly reflected. This is evidenced by the 114 signs of the “eastern” complex of enamel congestion and the anterior fossa of the second lower molar. In general, the comparative analysis definitely indicates the similarity of the Actors with the series Kultobe (South Kazakhstan), Old Terbez, Dalverzintepe (Uzbekistan). Key words: archaeology, burial mounds, monuments, anthropology, odontology, paleoanthropology, craniology, erasure, complex, typological.